Window on humanity a concise introduction to anthropology - Kottak, Conrad Phillip (New York McGraw-Hill, 2010)
What is Anthropology: Culture; Ethics and methods; Evolution, genetics, and human variation; The primates; Early hominins; The genus homo...
Includes bibliographical references (p. 465-495) and index.
Keywords: Anthropology; Xã hội học; Nhân chủng học